Insights from Benin's EtriLabs - Agbokou, Louis (Technical Centre for Agricultural and Rural Cooperation, 2016)
Technology hubs give young innovators and entrepreneurs the unique opportunity to develop their products and services and to make them marketable. The lack of awareness about the opportunities that e-agriculture has to offer, is one of the main obstacles to succeed.